New records of the Peruvian crevice-dwelling bat Tomopeas ravus (Chiroptera: Molossidae): What do they mean for its conservation?; Nuevos registros del murciélago peruano de grietas Tomopeas ravus (Chiroptera: molossidae), ¿qué significan para su conserva - Zeballos, H.; Pino, K.; Ludeña, J.P.; Escóbar, A.C.; Pari, A.; Medina, C.E.; Ceballos, G. (SAREM Sociedad Argentina para el Estudio de los Mamiferos, 2019)
The Peruvian crevice-dwelling bat, Tomopeas ravus, is a rare, threatened, and endemic species to the coastal desert from Peru. Recently, new records of the species after almost 30 years of absence in invento-ries were made, in the north and center of its distribution at localities from Ica and Piura departments, which opens discussions about the knowledge of its rarity, conservation status, and natural history. Here we present new records for this taxon and extend its geographic range by 260 km southwards of its known distributional range renewing the discussion on the conservation status of this species and its habitats, and proposing ac-tions for its conservation.
Keywords: Zoology; Geography; Biology; https://purl.org/pe-repo/ocde/ford#1.06.11